What characterizes Vacationers ’ eWOM sharing behaviours? Unbundling Entertainment and Information Motives in Brand-related Social Media Sites - Thomas, Tumsifu Elly; Kanje, Patrokil (University of Dar es Salaam Library Journal, 2021)
eWOM has increasingly become one of the sources of information relied on by vacationers to decide on where to go and where to stay. This article examines the influence of motivation on electronic word of mouth (eWOM) behaviour among vacationers in Tanzania. Four motivation variables from motivational psychology literature and the Uses and Gratification Theory (information, altruism, social integration and entertainment) are examined along three eWOM dimensions, namely giving, seeking and passing. Data was collected using a structured questionnaire from 278 vacationers at three airports in Tanzania who had used social media for their trip. The data was analysed using structural equation modelling. The overall results indicate that vacationers ' eWOM behaviours are positively related to entertainment motivation. Alongside entertainment, eWOM giving and seeking behaviours are positively related to information and social integration, respectively, and eWOM passing is positively related to altruistic motivation. Thus, the study concludes that entertainment motivation is the main driver of social media eWOM behaviours, hence a deviation from the past research that associated people ' s participation in eWOM with information motives.